2006
DOI: 10.1136/ard.2006.055137
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism at position +896 of the toll-like receptor 4 gene interferes with rapid response to treatment in rheumatoid arthritis

Abstract: The aim of this study was to determine whether the +896 ARG substitution of the Toll-like receptor 4 (TLR4) gene, causing the Asp299RGly change in the extracellular domain of TLR4, influences treatment response in recent-onset rheumatoid arthritis. 169 patients with rheumatoid arthritis were genotyped from the Finnish Rheumatoid Arthritis Combination Therapy trial, in which they were treated either with only one disease-modifying antirheumatic drug (DMARD) with or without prednisolone (single group), or with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 12 publications
2
18
1
1
Order By: Relevance
“…In the present study, meta-analysis of the TLR4 Asp299Gly polymorphism failed to reveal any association with RA susceptibility in Europeans. The single case-only study found that DAS28 differed significantly in RA patients according to the presence of this polymorphism (Kuuliala et al, 2006), but the 3 case-control studies failed to identify an association between this polymorphism and the clinical characteristics of RA (Kilding et al, 2003;Radstake et al, 2004;Sheedy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, meta-analysis of the TLR4 Asp299Gly polymorphism failed to reveal any association with RA susceptibility in Europeans. The single case-only study found that DAS28 differed significantly in RA patients according to the presence of this polymorphism (Kuuliala et al, 2006), but the 3 case-control studies failed to identify an association between this polymorphism and the clinical characteristics of RA (Kilding et al, 2003;Radstake et al, 2004;Sheedy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies met the study inclusion criteria (Kilding et al, 2003;Radstake et al, 2004;Sanchez et al, 2004;Kuuliala et al, 2006;Lee et al, 2006;Kang and Lee, 2007;Sheedy et al, 2008;Jaen et al, 2009;Enevold et al, 2010;Zheng et al, 2010;Etem et al, 2011 (Table 1). These studies involved 2078 patients with RA and 2581 controls.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations